Reconstruction of Allen's type IV fingertip amputation via bilateral unequal-sized hallux osteo-onychocutaneous free flaps: A retrospective study with 5-year follow-up - Xiu-Zhong Li; Xiu-Yun Wang; Yi-Min Zhou; Da-Zhi Yu; Hua-Gang Zhang; Shu-Jian Hou; Ke-Cheng Lao; Xiao Fan (Chinese Journal of Traumatology)
Purpose: The reconstruction of Allen's type IV fingertip amputation is a clinical challenge. Our team designed bilateral unequal-sized hallux osteo-onychocutaneous free flaps for the long-term reconstruction of Allen's type IV fingertip amputation and conducted a retrospective study with a 5-year follow-up aims to evaluate the effects of this technique. Methods: A retrospective analysis with a 5-year follow-up including 13 patients with Allen's type IV fingertip amputation who were admitted to our hospital from January 2010 to January 2017 was conducted. The patients were treated with bilateral unequal-sized hallux osteo-onychocutaneous free flaps. The operation time, intraoperative blood loss, and complications were recorded, and the survival rate of the transplanted flaps was calculated. During the 5-year follow-up after operation, the nail growth time was recorded and the finger appearance was observed. At the last follow-up appointment, the length, width, and girth of the reconstructed fingertip and contralateral normal fingertip, range of motion of the reconstructed fingertip and contralateral normal fingertip, Semmes-Weinstein test (for the evaluation of tactile sensation), and two-point discrimination testing results were recorded. SPSS 22.0 software was used for the statistical analysis and the data are presented as mean ± SD. Results: The mean operation time was (5.62 ± 0.51) h, the mean intraoperative blood loss was (34.15 ± 3.13) mL, and the survival rate of the transplanted flaps was 100%. During the 5-year follow-up, the average nail growth time was (10.14 ± 1.98) months and the average bone union time was (3.78 ± 0.91) months. The length, width, and girth of the reconstructed fingertip were (31.52 ± 3.73) mm, (17.82 ± 1.74) mm, and (59.75 ± 3.04) mm, respectively, which did not differ from those of the contralateral normal fingertip. The range of motion of the reconstructed fingertip was (12.15 ± 2.79) degrees which is different from that of the contralateral normal fingertip. The average tactile sensation evaluated via the Semmes-Weinstein test and the average two-point discrimination test of the reconstructed fingertip were (0.39 ± 0.17) g and (7.46 ± 1.14) mm, respectively, which were not different from those of the contralateral normal fingertip. The average Maryland score of feet in the donor area was 87.66 ± 7.39, which was satisfactory. Conclusion: Bilateral unequal-sized hallux osteo-onychocutaneous free flaps are an effective method to reconstruct Allen's type IV fingertip amputations with a satisfactory appearance and good sensory function.